Labelling phobias - new form of non-tariff barriers in international trade for tropical timber and wood / Assoc. Prof. Dr. Arshad Hashim (Universiti Teknologi MARA, Sarawak, 1996)
Recently, NGOs such as Green Peace, Friend of the Earth, Earthaction, World Wide Life Fund (WWF) and many others, have propagated environmental thinking and forcibly campaigned their respective legislators to label the tropical products as green and eco-friendly. In the US, the American Soybean Association (ASA), American Heart Savers' Association and other interest groups have lobbied the American Congress and the Food and Drug Administration (FDA) to label tropical oils and fats (palm oil, palm kernel and coconut oils) as saturated fats. Moll (1987) deliberately labelled and grouped palm oil as lauric oil although the fatty acid composition of palm oil is far from being lauric (i.e. 0.03% of lauric acid; Goh, 1991). Iran is the only country in the world that insists on labelling palm oil as "not fit for human consumption" despite the fact that more than a hundred other countries are importing and using palm oil for edible purposes. Recently, the rubber industry was again thrown into confusion after a paper was published in the US allegating that natural rubber products contain "harmful" substance which presumably could affect the health of the users. In other European countries, such as Holland and Austria, the local NGOs have demanded that tropical timber and furniture be conspicuously labelled as tropical timber for easy identification and subjected to boycott (Ahmad, 1994).